Hybrid vigor studies for different yield contributing traits in wheat under normal and heat stress conditions - Farooq, Jehanzeb; Khaliq, Ihsan; Akbar, Muhammad; Kashif, Muhammad; Mahpara, Shahzadi (Comunicata Scientiae, 2013)
Terminal heat stress is among one of the major constraints in wheat productivity in many countries of the world including Pakistan. To combat this natural calamity,one hundred spring wheat genotypes were assessed for heat stress tolerance under plastic sheet tunnel resulting in seven parents with varied heat stress tolerance. The seven parents including tolerant, moderately tolerant and susceptible but high yielders were later hybridized in a 7×7 diallel fashion. Analysis of variance revealed significant differences for all the studied traits.The heterosis and heterobeltiosis estimates revealed that thereisdesirable hybrid vigor in the current studies for all the traits evaluated.For grain yield maximum heterosis of 28.70% under normal and 27.02% under heat stress conditions were observed. Regarding heterobeltiosis it remained at 15.58% under normal and 13.62% under heat stress conditions. Similarly desirable negative results were obtained for relative cell injury%, days to heading and maturity and positive significant heterosis and heterobeltiosis was obtained for flag leaf area, biomass per plantand harvest index%. The cross combinations like Inqilab-91×Shalimar-88, Shalimar-88 × Maya/Pavon, Chenab-2000 × Punjab-85, Maya/Pavon × Chenab-2000, Shalimar-88 × Uqab-2000 and Uqab-2000 × Maya/Pavonhave shown good hybrid vigor in terms of various traits studied. Suggestively, they may be further exploited following pedigree or bulk method to develop heat tolerant wheat varieties because of their ability to perform well under normal and even diverse environments.